Condições de trabalho e distúrbio de voz em professores da rede estadual de ensino da cidade de Manaus, Amazonas, Brasil - Dias, Ivy Roberta Martins (2018)
Introduction - in the teaching profession, voice is a relevant factor for the teacher's performance in the classroom, especially as a constituent component of the teacher's identity as a worker. The teacher is among voice professionals with greater occurrence of complaints and voice disturbance caused by the use of voice in an inadequate context, either the environment or the work organization. Objectives - to analyze the occurrence of voice disturbance among the teachers of the state school of Manaus - AM and verify its association with demographic, functional, environmental and work organization characteristics. Methods - observational and cross - sectional research, in which teachers from elementary and middle school of the state teaching network of the city of Manaus participated. A stratified sample, composed of seven strata, each coming from one of the district coordinates of Manaus, was considered by statistical calculation. Sampling was done by conglomerate, where the schools drawn, and all teachers of those schools, were to be interviewed. The order of draw for schools of each coordination was respected. Participants answered the printed instruments: Vocal-Teacher Production Condition and Voice Disorder Screening Index. The descriptive analysis of the data was done through the means, standard deviations, minimum and maximum values of the quantitative variables and the absolute values and proportions for the qualitative variables. The chi-square and Fisher exact association tests were used for categorical variables to assess factors associated with voice disorders. Results - 453 teachers participated in the study, distributed in 39 schools, 310 female (68.4%), aged 41.3 years, 46.8% with a mean of 12.8 years and 54.1 % working in a single school. The characteristics of the work environment with the highest prevalence of inadequacy were the presence of noise in the school (80.6%) and in the work organization, the presence of stress (87.4%). The most frequent symptoms were dry throat (59.6%), hoarseness (58.7%), and fatigue on speech (50.8%). The presence of voice disorder was present in 46.1% of teachers. Factors associated with this presence were: demographic variables: female gender, younger age, marital status without some form of union; functional variables: none; work environment variables: inadequate conditions for: noise, noise intensity, absence of adequate rest space; and variables of work organization: inadequate conditions regarding: stressful work pace, repetitiveness at work, and all variables linked to situations of violence in the school. Conclusions: This study demonstrated a high prevalence of voice disturbance among teachers in the Manaus state school system, and factors such as presence of noise in school, noise intensity, stress and presence of violence are directly associated with the voice disorder found in these teachers